2009
DOI: 10.1007/s12010-009-8735-4
|View full text |Cite|
|
Sign up to set email alerts
|

α-Amylase: An Ideal Representative of Thermostable Enzymes

Abstract: The conditions prevailing in the industrial applications in which enzymes are used are rather extreme, especially with respect to temperature and pH. Therefore, there is a continuing demand to improve the stability of enzymes and to meet the requirements set by specific applications. In this respect, thermostable enzymes have been proposed to be industrially relevant. In this review, alpha-amylase, a well-established representative of thermostable enzymes, providing an attractive model for the investigation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
1
23

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 125 publications
(117 reference statements)
0
99
1
23
Order By: Relevance
“…Most of the enzymes are unable to perform the catalytic activity at high temperature values of 50-60ºC (27). The α-amylase in this study has been found to have optimum activity at 60ºC and retain more than 85% of its activity at high temperatures of 70-80ºC, which are considered as thermophilic range for enzymes (28,29).…”
Section: Discussionmentioning
confidence: 68%
“…Most of the enzymes are unable to perform the catalytic activity at high temperature values of 50-60ºC (27). The α-amylase in this study has been found to have optimum activity at 60ºC and retain more than 85% of its activity at high temperatures of 70-80ºC, which are considered as thermophilic range for enzymes (28,29).…”
Section: Discussionmentioning
confidence: 68%
“…All known -amylases, with a few exceptions, contain a conserved Ca 2+ binding site which is located at the interface between domains A and B (Linden et al, 2003;Prakash & Jaiswal, 2010). In addition, -amylase produced by Bacillus thermooleovorans was found to contain a chloride ion binding site in their active site (Malhotra et al, 2000), which has been shown to enhance the catalytic efficiency of the enzyme, presumably by elevating the pKa of the hydrogen-donating residue in the active site (Prakash & Jaiswal, 2010).…”
Section: Modular Structurementioning
confidence: 99%
“…In addition, -amylase produced by Bacillus thermooleovorans was found to contain a chloride ion binding site in their active site (Malhotra et al, 2000), which has been shown to enhance the catalytic efficiency of the enzyme, presumably by elevating the pKa of the hydrogen-donating residue in the active site (Prakash & Jaiswal, 2010). …”
Section: Modular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Більшість а-амілаз є металовмісними ферментами, активність яких може змінюватися у присутності іонів металів, які здатні виявляти акти вуючу чи інгібуючу дію. Зазвичай а-амілази містять у своїй структурі іони Са2+, які разом з іоном Na+ утворюють тріаду металів, що відіграє важливу роль у стабілізації білкової молекули та її стійкості до термічної інактивації [21].…”
unclassified